ANTROPOMETRIC PROFILE OF PROFESSIONAL PLAYERS OF FUTSAL: A COMPARATIVE STUDY AMONG DIFFERENT COMPETITIVE LEVELS AND FOR TACTICAL POSITION OF GAME (Fiep Bulletin - online, 2014)
The present study intended to do a characterization anthropometric of professional players of Futsal and compare them starting from different competitive levels and for tactical position carried out in the game. The sample was composed by 40 professional players of Futsal, chosen intentionally, belonging to three teams that disputed the championship of the state of the south of Brazil of Futsal organized for the league of Futsal of the state of the south of Brazil, in the three available categories, series gold of the year 2001 (it equips of Ipiranga Futebol Clube), series silver year 2000 and series bronze year 1999 (teams of the Esporte Clube Itapagé). The total body mass, stature, percentile of body fat and length body-cranium they were analyzed through Analyses of Variance (ANOVA) among the teams and enter the game positions. The test " t " was used for data only contained in two groups. The data evidenced a similarity of the teams among the different technical levels for all the analyzed variables. However, they point a differentiated characteristic of the lines in relation to the other positions in what it refers to the total body mass, suggesting a possible morphologic differentiation of the players that they act in this tactical function.
Keywords: Anthropometric; competitive levels; Futsal